2017
DOI: 10.5858/arpa.2016-0234-cp
|View full text |Cite
|
Sign up to set email alerts
|

False-Negative Interpretation of Adenocarcinoma In Situ in the College of American Pathologists Gynecologic PAP Education Program

Abstract: - The low correct interpretation rate and higher false-negative rate for AIS demonstrate the difficulty in interpreting AIS on Pap cytology, which may cause clinical consequences. The higher false-negative rate with pathologists than with cytotechnologists suggests cytotechnologists' higher screening sensitivity for AIS or cautious interpretation to avoid false-positive results by pathologists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
(23 reference statements)
0
7
0
2
Order By: Relevance
“…Desde a década de oitenta, estudos avaliando o exame de Papanicolaou revelam altas taxas de resultados falso-negativos, podendo chegar a 62% [Gay et al 1985, Bosch et al 1992, Silva 2005, Koonmee et al 2017, as causas dessa limitação ocorrem devido a erros de coleta, escrutínio e interpretação diagnóstica [Amaral et al 2008, Siddegowda et al 2016, Zhao et al 2017. Os erros relacionados a interpretação diagnóstica acontecem quando o citopatologista reconhece células alteradas, mas as classifica erroneamente.…”
Section: Contextualizaçãounclassified
See 1 more Smart Citation
“…Desde a década de oitenta, estudos avaliando o exame de Papanicolaou revelam altas taxas de resultados falso-negativos, podendo chegar a 62% [Gay et al 1985, Bosch et al 1992, Silva 2005, Koonmee et al 2017, as causas dessa limitação ocorrem devido a erros de coleta, escrutínio e interpretação diagnóstica [Amaral et al 2008, Siddegowda et al 2016, Zhao et al 2017. Os erros relacionados a interpretação diagnóstica acontecem quando o citopatologista reconhece células alteradas, mas as classifica erroneamente.…”
Section: Contextualizaçãounclassified
“…Como o exame de Papanicolaoué preventivo, ou seja, de rastreio, então a maioria dos casos analisados pelos citopatologistas apresentam resultados normais, em torno de 90% a 97%, considerando que oíndice de positividade deve estar entre 3 a 10% de acordo com o preconizado pelo Ministério da Saúde [Tobias et al 2016]. Portanto, somente uma pequena parte da rotina dos esfregaçosé direcionada para a observação de casos positivos, raros ou infecções incomuns e os profissionais muitas vezes têm contato muito esporádico com alguns tipos de lesão, o que gera insegurança na liberação do resultado e pode levar a uma classificação equivocada da lesão muitas vezes culminando em erro diagnóstico [Siddegowda et al 2016, Zhao et al 2017.…”
Section: Contextualizaçãounclassified
“…Approximately 50% of AIS was found by biopsy or puncture for high-grade or invasive squamous lesions [4]. The false negative rate was as high as 3.8% -11.7% which is easy to cause clinical missed diagnosis [5].Even if the combination with cytology colposcopy cervical multi-point biopsy and endocervical curettage pathology, atypical glandular cells were diagnosed in 3-4% AIS and 2% invasive cervical adenocarcinoma [6]. Recognizing AIS in cervical cytology is challenging.…”
Section: Introductionmentioning
confidence: 99%
“…11 Conversely, studies of these programs have identified repair as among the most common false-negative interpretations for squamous cell carcinoma, high-grade squamous intraepithelial lesion (HSIL), and adenocarcinoma in situ. [12][13][14] Multiple studies, using both CAP program slides and still images, have identified reparative changes as a diagnostic category with poor interobserver reproducibility. [15][16][17] Studies of the CAP glass slide programs looked specifically at the performance of reparative changes in 2001 and again in 2005.…”
mentioning
confidence: 99%
“…However, when significant lesions are misclassified as benign, repair is among the most common reasons for a false-negative misclassification. [12][13][14] Misclassification as repair was significantly more common among pathologists than cytotechnologists. These findings, in conjunction with the difference in performance in the Pap PT program, suggest that cytotechnologists may be predisposed to overcall difficult cases as dysplasia or malignancy (falsepositive misdiagnosis), and pathologists, conversely, more likely to undercall those cases as repair (false-negative misdiagnosis).…”
mentioning
confidence: 99%